NLRP3 Mediates NOXs-Induced Iron Overload and Inflammation but Not Oxidative Damage in Colons of DSS-Treated Mice - Yu L; Wang M; Zhou Y; Qi J; Zheng Q; Song Z (Journal of Inflammation Research)
Linna Yu,1,2,* Meng Wang,3,* Yunjiao Zhou,1,2 Jialong Qi,1,2 Qingqing Zheng,2,4 Zhengji Song1,2 1Department of Gastroenterology, The First People’s Hospital of Yunnan Province, Kunming, Yunnan, People’s Republic of China; 2The Affiliated Hospital of Kunming University of Science and Technology, Kunming, Yunnan, People’s Republic of China; 3Department of Hematology and Oncology, Guangzhou Women and Children’s Medical Center, Guangzhou Medical University, Guangzhou, Guangdong, People’s Republic of China; 4Department of Pathology, The First People’s Hospital of Yunnan Province, Kunming, Yunnan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhengji Song, Department of Gastroenterology, The First People’s Hospital of Yunnan Province, Kunming, Yunnan, People’s Republic of China, Email song4715@163.comBackground: Ulcerative colitis (UC) is an inflammatory bowel disease (IBD) with chronic and recurrent characteristics caused by multiple reasons, including iron overload, intestinal inflammation, and barrier dysfunction. Here, we investigated the effects of chemical inhibition of NOXs and NLRP3 activity on colonic iron metabolism and inflammatory reactions in a murine model of dextran sodium sulfate (DSS)-induced ulcerative colitis.Methods: The mice were randomly divided into five groups: normal control group, DSS-induced ulcerative colitis model group (DSS), DSS + Dapansutrile group, DSS + Diphenyleneiodonium chloride group, and DSS + Dapansutrile + Diphenyleneiodonium chloride group. On day 14, the mice were euthanized. Tissues were collected and analyzed to determine the effects of chemical inhibition of NOXs and NLRP3 activity on colonic iron metabolism and inflammatory reactions of dextran sodium sulfate-induced ulcerative colitis. Measurements such as weight, disease activity index, HE staining, Prussian blue staining, immunohistochemical and immunofluorescence, ELISA, flow cytometry detection, Western blot, and Quantitative Real-Time PCR were conducted.Results: Chemical inhibition of NOXs and NLRP3 in vivo could significantly reduce colonic iron overload and macrophage infiltration, thus alleviating colonic inflammatory response and tissue damage. Notably, the inhibition of NOXs significantly inhibited the expression of NLRP3 and oxidative damage, but the inhibition of NLRP3 had no significant effect on the expression of NOXs and oxidative damage, suggesting NOXs may exert their effects other than oxidative damage through NLRP3.Conclusion: To our knowledge, this work is the first to reveal that NLRP3 mediates NOXs-induced colonic iron overload and inflammation rather than oxidative damage in ulcerative colitis murine model, suggesting that the NOXs might promote ulcerative colitis by inducing colonic iron overload and macrophage infiltration dependent or partially dependent on NLRP3, as well as oxidative damage independent of NLRP3, which imply that both NOXs and NLRP3 are attractive targets for anti-colitis therapy.Keywords: ulcerative colitis, NADPH oxidases, NLRP3 inflammasome, iron overload, ROS, inflammation